Rate of Infection in Open Fracture of Long Bones with Delayed Debridement - Das, Manoj; Pandey, Suresh; Das, Anilata (Journal of College of Medical Sciences-Nepal, 2025)
Background The spectrum of open fracture ranges from small puncture wounds to extensive soft tissue injuries, periosteal stripping, and comminution of bone. Traditionally, timing of surgical debridement has been within 6 hours of injury often referred as “6-hour rule”. Though there is consensus on early debridement, there are various reasons for delay in surgical debridement, particularly in developing countries. This study aimed to assess the rate of infection in open fractures of long bones with delayed debridement. Methods This was observational study of retrospective data of 76 open fractures of long bones in adults. Data from all the patients with open fractures of long bones admitted and managed with delayed debridement (>6 hours) in between August 2018-January 2023 were collected and analyzed. Descriptive statistics was used to calculate frequency and percentage. Rate of infection in open fracture with delayed debridement was the main outcome assessed. Results The mean time of injury to surgical debridement was 28.18 hours (range 8-120, SD±24.61). Overall infection rate in open fractures with delayed debridement was 18.42% (n=14). The rate of infection in Gustilo Anderson grade I, II and III open fracture was 12.5% (n=2), 13.15% (n=5) and 31.81% (n=7) respectively. Conclusions The present study revealed a higher rate of infection associated with delayed debridement. Despite unique logistical challenges encountered in developing countries, the timely debridement by experienced surgeon may contribute to reduction in infection rate in open fractures.